Development of multi-drug resistance to anticancer drugs in HepG2 cells due to MRP2 upregulation on exposure to menthol - Nagai, Katsuhito; Tamura, Mayuko; Murayama, Ryuga; Fukuno, Shuhei; Ito, Takuya; Konishi, Hiroki (PloS one, 2023)
Background Menthol exerts relaxing, antibacterial, and anti-inflammatory activities, and is marketed as a functional food and therapeutic drug. Aim In the present study, the effects of menthol on the expression of multidrug resistance associated protein 2 (MRP2) and its association with the cytotoxicity of epirubicin (EPI) and cisplatin (CIS) were examined using HepG2 cells. Methods The expression levels of target genes were examined by real-time PCR. The intracellular concentration of incorporated EPI was measured by high-performance liquid chromatography. Cell viability was evaluated by MTT analysis. Results The expression of MRP2 mRNA was increased by exposing HepG2 cells to menthol for 24 hr. Consistent with a previous report suggesting an inverse correlation between MRP2 and Akt behavior, increased expression of MRP2 was also observed on suppression of the Akt function. Intracellular accumulation of EPI was significantly decreased by exposure of HepG2 cells to menthol, and a significant decrease in the intracellular concentration of EPI remaining was observed in HepG2 cells exposed to menthol. The decreased intracellular accumulation of EPI was significantly suppressed by treatment with MK-571, but not verapamil. Both EPI and CIS exerted cytocidal effects on HepG2 cells, but the decrease in cell viability was significantly attenuated by 24-hr menthol pre-exposure. Conclusion These results demonstrate that menthol causes hepatocellular carcinoma to acquire resistance to anticancer drugs such as EPI and CIS by MRP2 induction.